Uruguay : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Uruguay. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2022)
Uruguay entered the pandemic with solid institutions and social cohesion but growing macroeconomic imbalances-especially slow economic growth and weak public finances-as the end of the last commodity price boom in 2014 uncovered structural weaknesses. A new government came to power in March 2020 with a mandate to boost growth and restore fiscal sustainability. Legislation setting the foundations for many of the reforms has been passed and implementation is advancing--including on a new fiscal rule, and state-owned enterprise (SOE) and pension reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; France